Stefan Themerson’s Opera (St. Francis & The Wolf of Gubbio or Brother Francis’ Lamb Chops) - Hejmej, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper focuses on the experimental work of Stefan Themerson (St. Francis and The Wolf of Gubbio or Brother Francis’ Lamb Chops, an Opera in 2 Acts, text and music by Stefan Themerson, drawings by Franciszka Themerson, De Harmonie – Gaberbocchus Press, Amsterdam–London 1972) and the question of intermediality in general. An interpretation of the ‘semantic opera’ (written in 1954–1960, as a continuation of Semantic Divertissements [1962] and factor T [1956]), places Themerson’s idea in the context of the aesthetics of intermediality. The author signals a terminological confusion connected with the understanding of St. Francis and The Wolf of Gubbio (semantic opera; hybrid work; intermedial work, etc.) and argues that the aesthetics of intermediality appear to be an important and inspiring context for the interpretation of Themerson’s text and life. In this case, considerations on the subject of textuality show, on the one hand, different relations between literature, painting, music and theatre (artistic intermediality), and, on the other, the phenomenon of intermediality as the aesthetics of existence.